Não-cumulatividade do ICMS no discurso jurídico - Silva Júnior, José Wellington Maia da (2020)
The present work is constituted by bibliographic research with the purpose of exploring and explaining a legal-constitutional rule of the non-cumulativeness of the state value added tax (ICMS), taking into consideration the general aspects of the subject and necessary explanation for the construction of the legal rule and, withal, the magnitude that the constituent of the Constitution of the Federative Republic of Brazil has intended to give rise to the non-cumulativeness of the ICMS. It was assumed that the noncumulative aspect of ICMS in the Constitution of the Federative Republic of Brazil of 1988 is extensive and cannot be completely reach by neither thorough a formal logic nor by a syllogistic reasoning, which is typical of a classical legal positivism, since such content is related to a historical social interest against to the damaging cascade collection of sales tax, whose interest - universal and legitimate - cannot be detached from the positive law. Thus, it was agreed to present the history of sales taxes and the creation of tax non-cumulativeness in Europe, with an explanation of the main basic characteristics of value added tax (VAT). In this sense, this study intended to demonstrate and identify the social interest associated with non-cumulative tax approach, and how such interest was applied by the legislator. Subsequently, the same historical work was dedicated to Brazil, considering the Constitution of the Federative Republic of Brazil of 1988 and the jurisprudence of the Supreme Court (STF) regarding the non-cumulative nature of ICMS. At this stage, the study has not been focusing on the jurisprudence, but it has also taken in consideration a legal dogmatic with the purposes of critically exposing on how the non-cumulative nature of ICMS has been articulated in the Brazilian tax system. Finally, it was concluded that the construction of a constitutional rule concerning non-cumulative aspects of ICMS requiresmore than an interpretation of the legal concepts employed by the constituent, since its true content oscillates between the formal elements of Law and external data/info of the Law: social interest contrary to tax cumulativeness, which match up with the material content of the principle of economic efficiency